2019
DOI: 10.12688/f1000research.19198.1
|View full text |Cite
|
Sign up to set email alerts
|

Emerging therapies in the management of macular edema: a review

Abstract: Macular edema (ME) is a major complication of several vascular and inflammatory retinal diseases. Multiple mechanisms are implicated in its development and lead to visual impairment that could be reversible (the acute stages) or not reversible (long-standing ME). For this reason, an effective approach to the treatment of ME is of paramount importance in order to prevent irreversible damage of visual function. In this review, we discuss the management of ME and, in particular, current data of studies and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 99 publications
0
54
1
Order By: Relevance
“…However, an internationally accepted approach to uveitic macular edema has yet to be established. 43…”
Section: Discussionmentioning
confidence: 99%
“…However, an internationally accepted approach to uveitic macular edema has yet to be established. 43…”
Section: Discussionmentioning
confidence: 99%
“…Abicipar pegol (AGN-150998, MP0112, abicipar; Allergan plc/Molecular Partners) is an antagonist of VEGF-A characterized by small size, high potency, and long intravitreal half-life [ 15 , 152 ]. A phase I/II, open-label, multicenter dose-escalation trial, evaluating the safety and bioactivity of abicipar pegol in DME patients, found that there were prolonged edema reduction and improvement in vision [ 153 ].…”
Section: Treatment Strategies Of Dmementioning
confidence: 99%
“…Angiopoietins are a family of growth factors that bind to endothelial receptor tyrosine kinases [ 162 ]. Angiopoietin-2 is considered a key factor in DME pathogenesis (see Figure 1 ) [ 9 , 152 ].…”
Section: Treatment Strategies Of Dmementioning
confidence: 99%
“…Diseases of the macula can be acquired, multifactorial, or inherited. 4 Major progress in the diagnosis and treatment of macular diseases has led to clinical trials that seek to test if proposed therapies have both safety and efficacy (e.g., Reference 5 ). A key outcome in such trials has traditionally been best-corrected visual acuity (BCVA) using Early Treatment Diabetic Retinopathy Study (ETDRS) methodology to evaluate central vision.…”
Section: Introductionmentioning
confidence: 99%